13. konferenca Komisije za slovansko besedotvorje pri MSK - Stramljič Breznik, Irena (Slavia Centralis, 2020)
Report: 13th Conference of the Commission for Slavic Word Formation at MSK The author reported on the 13th conference of the Commission for Slavic Word Formation, which took place from 17 to 19 May 2011 in the Polish city Poznań.